A governança corporativa como um determinante da eficiência das organizações pertencentes ao setor elétrico brasileiro - Bernardino, Flávia Ferreira Marques (2014)
Due to dynamics of the globalized market companies in the Brazilian electric sector they deal with challenges and prospects for change, particularly with respect to the need to adopt methods and practices based on principles of governance in order to remain competitive and achieve better performance. However, the influence of corporate governance on organizational performance is still a problem without conclusive evidence, given the divergence in the results found by researchers. Address this problem the present study aimed to evaluate the effects of corporate governance practices on the different dimensions of organizational performance in Brazilian companies belonging to the Brazilian Electrical Sector, listed on the BM& FBovespa, in the period 2008-2012. For both analyzes of the regressions with panel data in order to investigate the relationship between the quality of governance in these companies and indicators of organizational performance were performed. Governance indices were constructed using the technique of principal component analysis, based on five of the governance mechanisms drawn from agency theory, namely: board of directors, ownership structure and control, protection of minority shareholders, transparency and remuneration administrators. As for organizational performance indicators were used in addition to traditional indices such as ROA, LAJIRDA, Tobin\'s Q, Market-to-book (MBA), an indicator of business efficiency, calculated by technical data envelopment analysis - DEA. The results show that the relationships investigated well governed companies perform better (efficiency), because the governance index showed a positive and significant association with performance when it was measured by a traditional performance indicator, the LAJIRDA and the efficiency score , pointing to the relationship expected by the literature on the subject. However, with respect to indicators of market value (Tobin\'s Q and MBA) results proved negative and statistically significant relationship between quality of governance and market value.